(untitled) (Global Journal of Management and Business Research, 2014)
This paper builds on previous studies and examines the barriers to strategy implementation by mid sized companies in Kenya. The study looks closely at the barriers which can either be internal; management, communication, human factors such as resistance to change, leadership, organizational structure, information systems and technology or external factors; changes to the operating environment, un-anticipated competition or entrants by new players in the industry and changes in government policies. It further recommends ways on how to overcome these barriers.